Clinical and molecular characteristics, therapeutic strategies, and prognosis of non-small cell lung cancer patients harboring primary and acquired BRAF mutations - Feng, Xiangran; Zeng, Ran; Lyu, Mengchen; Chen, Xiaoyan; Xu, Ziwei; Hu, Yue; Bao, Zhiyao; Sun, Xianwen; Zhao, Jingya; Zhou, Ling; Zhou, Jun; Gao, Beili; et al. (Frontiers in Oncology, 2025)
BackgroundThe differences in clinical characteristics and treatment prognosis in NSCLC patients harboring primary and acquired BRAF mutations are still poorly understood.MethodsFrom Oct 2017 to Dec 2023, 10, 211 lung cancer patients at Shanghai Ruijin Hospital were reviewed. 88 primary and 15 acquired BRAF-mutated NSCLC patients resistant to EGFR TKIs were included in the study.ResultsPrimary BRAF-mutated patients preferentially occurred in the elderly (median age: 67 vs 61, p=0.015), males (53.4% vs 26.7%, p=0.056), former/current smokers (36.5% vs 6.7%, p=0.033), non-adenocarcinoma (11.4% vs 0%, P=0.351) compared to acquired BRAF-mutated patients. Significant differences in gender (33.3% vs 62.3%, p=0.012), smoking history (22.2% vs 43.1%, p=0.063), and adenocarcinomas (100% vs 83.6%, p=0.028) were observed between primary BRAF/EGFR co-mutated and non-co-mutated groups. While primary and acquired BRAF/EGFR co-mutated patients had similar clinical characteristics, with EGFR mutations being the most common coexisting oncogene (30.7% and 93.3%). The genotype of EGFR mutations differed, with acquired BRAF-mutated cases showing more complexity and a higher rate of dual EGFR mutations (35.7%) compared to primary cases. For primary BRAF/EGFR co-mutated patients, no matter what kinds of therapies, the EGFR 19del patients had a better prognosis than non-19del patients, and the first line mPFS was NR and 9.0 months (95% CI: 7.7-10.3 months) (p=0.0062), respectively. Dabrafenib and trametinib plus 3rd EGFR TKIs improved the prognosis of primary BRAF/EGFR non-19del co-mutated patients, achieving ORR and mPFS of 100% (3/3) and 12 months. For acquired co-mutated patients, the mPFS for 5 patients was 8.6 months (95% CI: 5.4-11.8 months). No new safety concerns and > grade 3 AEs were noted.ConclusionTogether, our study demonstrates that primary and acquired BRAF-mutant patients show distinct differences in some clinical and molecular characteristics, but acquired BRAF/EGFR co-mutated and primary BRAF/EGFR non-19del co-mutated patients may both respond to triple-targeted therapy.